Nstar 2005 2006
DOI: 10.1142/9789812773333_0045
|View full text |Cite
|
Sign up to set email alerts
|

Eta Photoproduction Off the Neutron at Graal

Abstract: The γn → ηn quasi-free cross section reveals a resonant structure at W ∼ 1.675 GeV. This structure may be a manifestation of a baryon resonance. A priori its propreties, the possibly narrow width and the strong photocoupling to the neutron, look surprising. This structure may also signal the existence of a narrow state.Meson photoproduction off the neutron offers an attractive tool to study certain baryon resonances. A single-quark transition model 1 predicts only weak photoexcitation of the D 15 (1675) resona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Note that exactly the same self-consitent formalism and numerical methods are used in the present work. With this formalism used, we can describe pentaquark observables on the same ground as those for the octet baryons without doing any additional conceptual changes and using the same parameter set.In addition to the Θ + , a recent GRAAL experiment [21,22,23] has announced a new finding of the nucleon-like resonance around 1.67 GeV in the neutron channel, measuring the cross section of η photoproduction off the deutron. The corresponding width was found…”
mentioning
confidence: 99%
“…Note that exactly the same self-consitent formalism and numerical methods are used in the present work. With this formalism used, we can describe pentaquark observables on the same ground as those for the octet baryons without doing any additional conceptual changes and using the same parameter set.In addition to the Θ + , a recent GRAAL experiment [21,22,23] has announced a new finding of the nucleon-like resonance around 1.67 GeV in the neutron channel, measuring the cross section of η photoproduction off the deutron. The corresponding width was found…”
mentioning
confidence: 99%
“…1. We made very simple analysis of that phenomena using "speed characteristics" (6) in order to single out "rapid" contributions on the background of smooth contributions of known wide resonances. Our analysis showed that the data of [26] may indicate an existence of new narrow N * (1685) resonance with Γ tot ≤ 50 MeV and small resonance photocoupling in the range of Br ηN A p 1/2 ∼ (0.3 − 3) · 10 −3 GeV −1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently four groups -GRAAL [6,7], CBELSA/TAPS [8], LNS [9], and Crystal Ball/TAPS [10] -reported an evidence for a narrow structure at W ∼ 1680 MeV in the η photoproduction on the neutron. The structure was observed as a bump in the quasi-free cross section (the neutron anomaly * ) and as a peak in the invariant-mass spectrum of the final-state η and the neutron (M(ηn)) [7,8,10].…”
Section: Introduction To the Neutron Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Θ + , Kuznetsov et al [16][17][18] discovered a new nucleon-like resonance around 1.67 GeV from η photoproduction off the deutron in the neutron channel, based on the GRAAL data. The decay width was measured to be around 40 MeV.…”
Section: Introductionmentioning
confidence: 99%